Shaping the spectral characteristics of fiber Bragg gratings written in optical fiber taper using phase mask method - Osuch, Tomasz; Jędrzejewski, Kazimierz; Lewandowski, Lech; Jasiewicz, Wiesław (Photonics Letters of Poland, 2012)
Fabrication of fiber Bragg gratings using phase mask method, despite the substantial advantages, has a significant drawback. In this technique, the phase mask period determines Bragg wavelength, and thus limits the possibilities of shaping its spectral characteristics. The paper presents the possibility of modifying the transmission and reflection spectra of fiber Bragg gratings written in the thermally tapered optical fiber using complex UV irradiation through the uniform phase mask. Structures with two Bragg wavelengths and with narrow transmission band in spectral characteristics were achieved by modifying the amplitude of refractive index changes and effective index distribution along the fiber taper. Full Text: PDF References A. Othonos, K. Kalli, Fiber Bragg gratings: fundamentals and applications in telecommunications and sensing (Norwood, Artech House 1989). R. Kashyap, Fiber Bragg gratings, (Boston, Academic Press 1999). K. C. Byron, K. Sugden, T. Bricheno and Bennion, "Fabrication of chirped Bragg gratings in photosensitive fibre", Electr. Lett. 29, 1659 (1993). CrossRef T. Osuch, P. Gąsior, L. Lewandowski, "System for modification of exposure time in fiber Bragg gratings fabrication with using scanning phase mask method", Proc. SPIE 5775, 222 (2005). CrossRef